Correlation between Stress Levels and Self-Harm Behavior among College Students in Surabaya: Cross-Sectional: Mental Health Nursing - Andikawati Fitriasari; Dyah Ika Krisnawati; Chilyatiz Zahroh; Firdaus; Ragil Putri Fitriyanti (Journal Of Nursing Practice, 2025)
Background: Nursing students experience high stress levels because of the high demands, expectations and activities during their study. Therefore some students struggle to adapt to their college life, eventually resorting to dangerous behaviors such as self-harm, which they perceive as a coping mechanism to relieve stress. Purpose: This study aims to analyze the relationship between stress levels and self-harm incidents among active students at Universitas Nahdlatul Ulama Surabaya. Methods: This research design uses descriptive correlational with cross-sectional approach.  This study involved 293 students from Universitas Nahdlatul Ulama Surabaya, with purposive sampling technique. The dependent variable in this study is self-harm behavior, while the independent variable is the level of stress. The instrument tools used are the Perceived Stress Scale (PSS) questionnaire and DSHI (Deliberate Self Harm Inventory). Results: A total of 293 students were sampled in this study. The majority of stress levels were experienced by women, with 135 respondents experiencing moderate stress levels and 118 students having engaged in mild self-harm behavior. The results of the Spearman’s rank statistical test showed a significant correlation between stress levels and self-harm behavior (p-value = 0.004), indicating that higher levels of perceived stress are associated with a greater tendency toward self-harm Conclusion: This study concluded that the majority of students were under stress, with most perceiving themselves to be experiencing moderate stress. There is an urgent need to identify the underlying causes and implement effective management and preventive measures to mitigate the long-term negative effects of stress on students’ careers and well-being.